A Philosophical Reflection on Bates’ Definition of Information - Zhensong Wang (Proceedings, 2022)
This paper will analyze Marcia Bates’ definition on information from four perspectives, overall philosophical standpoint, ontological position, epistemological position, and methodological position. The viewpoints of four information specialists (Luciano Floridi, Marcia Bates, Fred Dretske, and Kun Wu) will be compared in the paper as well. At last, we will find Bates’ position in the information study, and also the merit and demerit of her definition on information.